Effects of Plant Growth Regulators and N Rate on the Morphological Traits of Generative Tillers and Seed Yields of Chewings and Strong Creeping Red Fescue - Małgorzata Szczepanek; Maciej Baczyński; Radomir Graczyk (Agronomy, 2020)
Plant growth regulators (PGRs) are used as a management tool to minimize plant height and subsequent stem lodging in grass seed crops. Their efficacy is influenced not only by the method of application, but also by the management and genetic variations within and between species. This aim of the study was to evaluate the effect of PGRs on morphological traits of generative tillers and seed yield of Festuca rubra L ssp. rubra (strong creeping red fescue) and F. r. L ssp. commutata (Chewings red fescue) under low and medium doses of spring nitrogen fertilization (40 and 70 kg N ha−1). PGRs were applied as: chlormequat chloride (CCC) at BBCH 30–31; CCC at BBCH 30–31 + ethephon (ET) at BBCH 37–39; CCC at BBCH 30–31 + trinexapac-ethyl (TE) at BBCH 37–39. All the application methods of PGRs resulted in the shortening of the second internode, and the sequential application of CCC with ET or TE also resulted in the shortening of the third internode. In each PGR treatment, the lodging index in the plant (canopy height to tiller length ratio) was higher than that of the control. PGRs had a beneficial effect on the seed yield. The greatest increase in the seed yield was recorded after the application of CCC+TE. No interaction between PGRs and spring N fertilization rates on the seed yield of red fescue. The increase in the dose of spring nitrogen fertilizer from 40 to 70 kg N ha−1 resulted in a significant increase in yield. Seed yield of chewing red fescue cv. Dorosa was 29% higher than strong creeping red fescue cv. Nista, mainly due to an increase in the number of generative tillers.